DAMPAK PANDEMI COVID-19 PADA INDUSTRI PERHOTELAN (STUDI KASUS DI HOTEL GRAND ORCHID YOGYAKARTA) - Ristanti Ristanti (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
This study aims to analyze the impact of the COVID-19 pandemic on the hospitality industry in Yogyakarta, especially the Grand Orchid Hotel Yogyakarta. This study used descriptive qualitative method. Primary data obtained from interviews, observations and interviews. The COVID-19 pandemic has had a very significant impact on the business of the Grand Orchid Hotel Yogyakarta. In terms of income and also the number of employees. Various things have been attempted to keep the hotel operational, namely by giving big discounts for rooms and dining menus in restaurants, making wedding packages with a limited number of guests. As a form of support to the Government regarding the implementation of various restrictions on activities, especially in hotels, Hotel Grand Orchid Yogyakarta has also received CHSE certification from the Ministry and also from the Sleman Regency Government. In addition, the Grand Orchid Hotel Yogyakarta also enforces the COVID-19 Health Protocol SOP for both guests and employees.Keywords: pandemic, hotel industry, grand orchid Yogyakarta